Lithium ion battery positive electrode material and preparation method and application thereof

By employing a core-shell structure and a stepwise sintering process in the cathode material of lithium-ion batteries, a composite coating layer of fast ion conductors and oxides is formed, solving the problems of rate performance and cycle stability of lithium-ion batteries under high power conditions, achieving efficient electron and ion transport, and improving the overall performance of the battery.

CN120998953APending Publication Date: 2025-11-21HUNAN CHANGYUAN LICO NEW ENERGY CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510945713.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing lithium-ion battery cathode materials have limited rate performance under high-power charge and discharge conditions, poor cycle stability, and are prone to side reactions caused by residual lithium on the surface and insufficient high-temperature stability, making it difficult to meet the needs of new energy vehicles.

Method used

The lithium-ion battery cathode material adopts a core-shell structure, with a lithium layered metal oxide at the center and a composite dual-phase coating layer and a carbon coating layer on the outside. The composite dual-phase coating layer is composed of fast ion conductors and oxides, and a complementary network is formed through stepwise sintering to optimize the ion and electron transport paths.

Benefits of technology

It significantly reduces interface impedance, improves the conductivity and stability of materials, extends battery life, enhances high-rate charge-discharge performance and cycle retention, and suppresses side reactions between electrode materials and electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120998953A_ABST
    Figure CN120998953A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery positive electrode material and a preparation method and application thereof. According to the lithium ion battery positive electrode material, the lithium ion battery positive electrode material has a core-shell structure, a lithium layered metal oxide, a composite double-phase coating layer and a carbon coating layer are distributed from the center to the surface of the lithium ion battery positive electrode material, and the composite double-phase coating layer is prepared from a fast ion conductor and an oxide. The lithium ion battery positive electrode material provided by the invention solves the problems of limited rate capability and poor cycling stability of a ternary material, improves the capacity retention ratio of a lithium ion battery under high-power charging and discharging conditions, inhibits interface side reaction between an electrode material and an electrolyte, and prolongs the service life of the battery. The invention also provides a preparation method and application of the lithium ion battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of lithium ion batteries, and particularly relates to a lithium ion battery positive electrode material and a preparation method and application thereof. BACKGROUND

[0002] With the rapid development of global new energy vehicle industry, the demand for power batteries continues to grow. As the current mainstream power battery technology, the performance of lithium ion batteries is largely dependent on the characteristics of the positive electrode material. Currently commercialized lithium ion battery positive electrode materials mainly include lithium iron phosphate (LFP), lithium cobalt oxide (LCO) and ternary materials (such as NCM, NCA). Among them, although lithium iron phosphate has high safety and long cycle life, its specific capacity and rate performance are poor, which limits its application in high-end electric vehicle field. Although lithium cobalt oxide has high energy density, the scarcity and high price of cobalt lead to high cost. In comparison, ternary materials have become the research hotspot of current power battery positive electrode materials due to their high energy density, good cycle performance and relatively low cost.

[0003] However, ternary materials still have many problems in practical application. First, with the increase of cycle times, structural phase transition occurs in the material, leading to capacity attenuation and significant increase of direct current resistance (DCR), which affects the power output and cycle life of the battery. Second, the residual lithium on the surface of ternary materials not only reduces the initial coulomb efficiency, but also causes side reactions with electrolyte, accelerating the performance degradation of the battery. In addition, the high-temperature stability of the material is poor, and thermal runaway easily occurs under high-temperature conditions, bringing safety hazards. With the increasing demand for plug-in hybrid electric vehicles and fast charging, the market demand for high-power lithium ion batteries is increasingly urgent, and the rate performance of existing ternary materials is still difficult to meet the requirements.

[0004] The key factors affecting the rate performance of lithium ion batteries mainly include lithium ion diffusion rate and electronic conductivity of the material. Currently, researchers usually adopt surface coating strategy to improve the performance of ternary materials. For example, fast ion conductors (such as perovskite, LISICON or NASICON materials) are widely used for surface modification of positive electrode materials due to their excellent lithium ion conductivity, in order to reduce the diffusion resistance of lithium ions, reduce electrode polarization and thus reduce the internal resistance of the battery (as described in patent CN110690435A). However, the electronic conductivity of fast ion conductors is poor, and the use of single coating material may lead to blocked electronic transmission, affecting the overall electrochemical performance of the material. On the other hand, although electronic conductivity compounds (such as metal oxides, carbon materials, etc.) can improve the electronic conductivity of the material, their hindering effect on lithium ion diffusion will limit the rate performance of the battery. Therefore, a single coating material cannot simultaneously optimize lithium ion transmission and electronic conduction, and it is urgent to develop a synergistic coating strategy to take into account the ionic conductivity and electronic conductivity of the material.

[0005] To solve the above problems, patent CN118299544A proposes a ternary positive electrode material coated with fast ion conductor and electron conductive compound to improve lithium ion diffusion and electron transport performance. However, the existing technology still has problems such as insufficient uniformity of the coating layer and low interface bonding strength, which affects the long-term stability and power performance of the material. Therefore, it is urgent to develop a new type of high-power lithium ion battery positive electrode material and its preparation method, which optimizes the composition and structure of the coating layer to significantly improve the rate performance and cycle stability of the material while ensuring high capacity, to meet the demand for high-power batteries for new energy vehicles. SUMMARY

[0006] The present application aims to at least solve one of the above technical problems in the prior art. To this end, the present application provides a lithium ion battery positive electrode material, which solves the problems of limited rate performance and poor cycle stability of ternary materials, improves the capacity retention rate of lithium ion batteries under high-power charging and discharging conditions, and suppresses the interface side reaction between the electrode material and the electrolyte, prolonging the service life of the battery.

[0007] The present application also provides a preparation method of a lithium ion battery positive electrode material.

[0008] The present application also provides a lithium ion secondary battery.

[0009] The first aspect of the present application provides a lithium ion battery positive electrode material having a core-shell structure, with a lithium layered metal oxide, a composite dual-phase coating layer and a carbon coating layer distributed from the center to the surface of the lithium ion battery positive electrode material. The preparation raw materials of the composite dual-phase coating layer include a fast ion conductor and an oxide.

[0010] One of the technical solutions of the present application related to the lithium ion battery positive electrode material has at least the following beneficial effects:

[0011] In the lithium ion battery positive electrode material of the present application, the preparation raw materials of the composite dual-phase coating layer include a fast ion conductor and an oxide. After sintering, the fast ion conductor and the oxide coat the lithium layered metal oxide, forming a complementary network of ion transport paths and electron transport paths, thereby reducing the overall interface impedance.

[0012] On the one hand, the composite dual-phase coating layer can reduce the direct contact between the electrode material and the electrolyte, inhibit the dissolution of transition metals and the decomposition of electrolyte; on the other hand, the high mechanical strength of the oxide combined with the flexibility of the fast ion conductor can alleviate the volume change during charging and discharging.

[0013] The surface of the composite dual-phase coating layer forms a heterojunction with the carbon coating layer, which further promotes electron migration through interface charge redistribution, and the two build a "three-dimensional conductive skeleton", and the electron transmission efficiency is significantly improved. The flexibility, high mechanical strength and chemical inertness of the carbon coating layer can inhibit the side reaction of the composite dual-phase coating layer with the electrolyte, thereby inhibiting the exposure of the electrode material, and the high flexibility can inhibit the volume expansion of the material during lithium extraction, thereby improving the stability of the electrode material.

[0014] At the interface of the heterojunction, due to the change of lattice constant and atomic periodicity, the electron binding energy and the height of the potential barrier will change, thereby affecting the behavior of the electrons, and the heterojunction interface will form a potential barrier, so that the electron and hole concentrations are different, which helps to improve the conductivity; the band gap width and the conductivity performance at the interface of the heterojunction are different from those of its adjacent crystals, and this difference can optimize the transmission of electrons, thereby improving the overall conductivity.

[0015] At the interface between graphene and the composite dual-phase coating layer, there is a change in the lattice constant and the atomic periodicity, which will cause a change in the electron binding energy and the height of the potential barrier, thereby affecting the behavior of the electrons. This interface characteristic can make the heterojunction have different potential differences, can form a potential barrier, has different band gap widths and conductivity performances, and this difference can optimize the transmission path of the electrons, thereby improving the overall conductivity.

[0016] Taking oxide WO3 as an example, in the composite dual-phase coating layer, WO3 acts as an n-type semiconductor and has high electron conductivity, which can provide a fast electron transmission channel for the electrode material and reduce the interface charge transfer impedance; the fast ionic conductor has high ionic conductivity, which can accelerate the diffusion of lithium ions. The composite dual-phase coating layer forms a complementary network of ion transmission paths and electron transmission paths, which significantly reduces the overall interface impedance. The co-coating layer can reduce the direct contact between the electrode material and the electrolyte, inhibit the dissolution of transition metals and the decomposition of the electrolyte. The high mechanical strength of WO3 combined with the flexibility of the fast ionic conductor can alleviate the volume change during charging and discharging.

[0017] The lithium ion battery anode material of the present application utilizes the combination of ionically conductive compounds and electronically conductive compounds to improve the conductivity of the material, reduce the DCR impedance, and improve the power performance.

[0018] According to some embodiments of the present application, the chemical formula of the lithium layered metal oxide is Li a Ni x Co y Mn z M wO2, wherein 1.03≤a≤1.3, 0.3≤x≤0.8, preferably 0.3≤x≤0.6, 0≤y≤0.4, 0≤z≤0.4, 0≤w≤0.1, x+y+z+w=1, M comprises at least one of Zr, W, Ti, Al, Nb, La, Sr, Ca, B, Ba, Mo and Ta.

[0019] According to some embodiments of the present application, 0.02≤w≤0.06.

[0020] According to some embodiments of the present application, M comprises at least one of Zr, W, Ti.

[0021] According to some embodiments of the present application, the composite dual-phase coating layer is obtained by sintering the fast ion conductor and the oxide.

[0022] During the sintering process, part of the oxide, such as Al2O3 or WO3, becomes lithium aluminate or lithium tungstate, which functions as an ion conductor; part of the oxide remains in its original state, which functions as an electron conductor.

[0023] According to some embodiments of the present application, the fast ion conductor comprises at least one of a NASICON-type fast ion conductor, a LISICON-type fast ion conductor and a perovskite-type fast ion conductor.

[0024] According to some embodiments of the present application, the NASICON-type fast ion conductor is a kind of fast ion conductor material that carries ions as charge carriers, and its name is derived from its high ion conductivity characteristics. This kind of material can realize the rapid migration of ions due to its three-dimensional open framework structure.

[0025] According to some embodiments of the present application, the NASICON-type fast ion conductor comprises at least one of lithium aluminum titanium phosphate (LATP), lithium zirconium phosphate (LZP), lithium phosphate and lithium aluminate.

[0026] According to some embodiments of the present application, the LISICON-type fast ion conductor is an oxide solid-state electrolyte that carries lithium ions as charge carriers, and its chemical composition has lithium as the core and can also contain aluminum, germanium, phosphorus, oxygen, sulfur, selenium, silicon, titanium, arsenic, chromium and other elements.

[0027] According to some embodiments of the present application, the LISICON-type fast ion conductor comprises at least one of LiZnGeO4, Li 3.5 Si 0.5 P 0.5 O4, Li 10 AlP2O 12 .

[0028] According to some embodiments of the present application, the perovskite-type fast ion conductor is a kind of material based on perovskite structure (ABX3), which is named for its special crystal skeleton structure that can realize fast migration of ions (such as oxygen ions, protons or lithium ions). Such materials exhibit excellent ionic conductivity under high temperature or specific doping conditions.

[0029] According to some embodiments of the present application, the perovskite-type fast ion conductor comprises Li 3x La 0.67-x TiO3, Li 3x Nd 0.67-x TiO3, La x Ag y Li 1-3x-y NbO3.

[0030] According to some embodiments of the present application, the fast ion conductor is a NASICON-type fast ion conductor.

[0031] According to some embodiments of the present application, the oxide comprises at least one of Zr, W, Ti, Al and Nb oxides.

[0032] According to some embodiments of the present application, the oxide comprises at least one of W, Ti and Al oxides.

[0033] Among W, Ti and Al oxides, tungsten oxide improves the overall performance of the battery by improving interface stability and material performance, and the oxide coating layer (such as WO3, Al2O3) can improve interface electron transport and improve rate performance. Oxides have high mechanical strength and high chemical stability, which can inhibit the reaction of electrode materials and electrolyte and improve the stability of the battery.

[0034] According to some embodiments of the present application, the carbon coating layer comprises at least one of graphene coating layer, carbon nanotube coating layer, glucose coating layer and sucrose coating layer.

[0035] According to some embodiments of the present application, the carbon coating layer comprises at least one of graphene coating layer and carbon nanotube coating layer.

[0036] Graphene and carbon nanotubes have ultra-high electronic conductivity (10 6 S / m) and two-dimensional continuous network structure, which provides a fast electron transport channel for electrode materials and reduces interface charge transfer impedance.

[0037] According to some embodiments of the present application, the lithium ion battery positive electrode material has a porous structure, which is beneficial to the full infiltration of electrolyte and the rapid transmission of lithium ions, reduces impedance and improves power performance.

[0038] According to some embodiments of the present application, in the porous structure of the lithium ion battery cathode material, part of the pores are through pores.

[0039] The prepared electrode material is secondary particles composed of primary particle agglomeration, the through pore structure is the pore between the primary particles, and the particle size of the additive used for coating is smaller than that of the primary particles, so it does not affect the through pore structure of the secondary particles.

[0040] The second aspect of the present application provides a method for preparing the lithium ion battery cathode material of the present application, comprising the following steps:

[0041] (1) mixing and sintering the precursor Ni x Co y Mn z (OH)2, a lithium source and a M-containing doping source, primary sintering in an oxygen atmosphere, and cooling to obtain a primary sintered product;

[0042] (2) mixing the primary sintered product with a fast ion conductor and an oxide, secondary sintering in an air atmosphere to obtain a secondary sintered product;

[0043] (3) mixing the secondary sintered product with a carbon coating agent, and tertiary sintering in a protective atmosphere to obtain a tertiary sintered product, i.e. the lithium ion battery cathode material.

[0044] The preparation method of the present application adopts a step-by-step coating method, taking Ni x Co y Mn z O2 as the core, and different additives are layered coated on the shell. The carbon material modifies the fast ion conductor to improve its conductivity, reduce impedance and improve power performance.

[0045] The present application adopts a gradient coating strategy to construct a multi-layer composite conductive structure: the first coating layer selects a fast ion conductor and an oxide. The fast ion conductor has high ion conductivity (σ_ion>10 -3 S / cm), but the electronic conductivity is relatively insufficient; the oxide (such as tungsten trioxide combined with lithium ions or combined with graphite carbon material) has excellent electronic conductivity (σ_ele=10 4 S / cm); through the design of a double-continuous phase structure, an electronic-ion double-continuous conduction path is constructed; the second coating layer uses graphitized carbon material, relying on its ultra-high electronic mobility (μ_e≈2×10 4 cm 2 / (V·s)) and three-dimensional network structure, and forms a heterostructure with the composite double-phase coating layer at the interface, which has a high-efficiency charge transport channel. The composite structure significantly reduces the interface impedance of lithium ion diffusion and electron migration (by more than 20%) through the multi-scale synergistic effect, and significantly improves the power performance of the material.

[0046] According to some embodiments of the present application, the sintering temperature of the first sintering is 700-900℃, and the time is 8-16h.

[0047] According to some embodiments of the present application, the sintering temperature of the first sintering is any one of 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 770℃, 780℃, 790℃, 800℃, 810℃, 820℃, 830℃, 740℃, 850℃, 860℃, 880℃, 880℃, 890℃, 900℃, such as 800℃, or a range value formed by any two, such as 800-830℃.

[0048] When the sintering temperature of the first sintering is too high, it may cause excessive grain growth or particle sintering agglomeration, increase the particle size difference, and at the same time cause cobalt / manganese element volatilization, destroy the material uniformity, form non-active phase (such as spinel phase) on the surface, and damage the rate performance and cycle life; when it is too low, it cannot complete the solid phase reaction, resulting in low material crystallinity, residual impurities, incomplete crystal structure, increased lithium-nickel mixing degree, and reduced lithium ion diffusion rate and initial discharge capacity.

[0049] According to some embodiments of the present application, the sintering temperature of the second sintering is 400-600℃, and the time is 6-14h.

[0050] According to some embodiments of the present application, the sintering temperature of the second sintering is any one of 400℃, 420℃, 440℃, 460℃, 480℃, 500℃, 520℃, 540℃, 560℃, 580℃, 600℃, such as 500℃, or a range value formed by any two, such as 500-540℃.

[0051] When the sintering temperature of the second sintering is too low, the composite double-phase coating layer cannot be uniformly formed or is too loose, the interface side reaction is intensified, and the coating effect is affected; when it is too high, the oxide may undergo phase change to generate non-conductive impurities, which is not conducive to electronic conduction.

[0052] According to some embodiments of the present application, the sintering temperature of the third sintering is 450-550℃, and the time is 6-14h.

[0053] According to some embodiments of the present application, the sintering temperature of the third sintering is any one of 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, such as 500℃, or a range value formed by any two, such as 480-520℃.

[0054] When the sintering temperature is too high, the two-dimensional structure of graphene is destroyed, resulting in a decrease in conductivity and mechanical strength; when the sintering temperature is too low, the coating effect is poor, and a heterojunction interface cannot be formed, thereby reducing the interface contact effect of the composite material.

[0055] The present application adopts a high-temperature solid-phase method to form a composite double-phase coating layer in a suitable temperature range. Lithium layered oxides, oxides and fast ion conductors are mixed at high speed, diffused at high temperature and restructured at the interface, and finally form a co-coating layer on the surface of the electrode particles.

[0056] According to some embodiments of the present application, in step (1), the added doping element M accounts for 0.06mol% to 1.5mol% of the molar percentage of elements (Ni+Co+Mn+M') in the precursor.

[0057] According to some embodiments of the present application, in step (1), the added doping element M accounts for 0.08mol% to 1mol% of the molar percentage of elements (Ni+Co+Mn+M') in the precursor.

[0058] According to some embodiments of the present application, in step (1), the added doping element M accounts for any one of 0.08mol%, 0.1mol%, 0.2mol%, 0.3mol%, 0.4mol%, 0.5mol%, 0.6mol%, 0.7mol%, 0.8mol%, 0.9mol%, 1mol% or any range formed by any two of them, such as 0.5mol% to 0.7mol%, of the molar percentage of elements (Ni+Co+Mn+M') in the precursor.

[0059] According to some embodiments of the present application, in step (2), the added coating source accounts for 0.06mol% to 2mol% of the molar percentage of elements (Ni+Co+Mn+M') in the precursor.

[0060] According to some embodiments of the present application, in step (2), the added coating source accounts for 0.08mol% to 1.5mol% of the molar percentage of elements (Ni+Co+Mn+M') in the precursor.

[0061] According to some embodiments of the present application, in step (2), the added coating source accounts for any one of 0.08mol%, 0.1mol%, 0.2mol%, 0.3mol%, 0.4mol%, 0.5mol%, 0.6mol%, 0.7mol%, 0.8mol%, 0.9mol%, 1mol%, 1.1mol%, 1.2mol%, 1.3mol%, 1.4mol%, 1.5mol%, such as 1mol%, or a range value formed by any two of them, such as 1mol%~1.5mol%, of the molar percentage of elements (Ni+Co+Mn+M') in the precursor.

[0062] According to some embodiments of the present application, in step (3), the added coating source accounts for 0.05wt%~0.5wt% of the mass percentage of elements (Ni+Co+Mn+M') in the precursor.

[0063] According to some embodiments of the present application, in step (3), the added coating source accounts for 0.08mol%~0.2wt% of the mass percentage of elements (Ni+Co+Mn+M') in the precursor.

[0064] According to some embodiments of the present application, in step (3), the added coating source accounts for any one of 0.08mol%, 0.1mol%, 0.2mol%, 0.3mol%, 0.4mol%, 0.5mol%, 0.6mol%, 0.7mol%, 0.8mol%, 0.9mol%, 1mol%, 1.1mol%, 1.2mol%, 1.3mol%, 1.4mol%, 1.5mol%, 1.6mol%, 1.7mol%, 1.8mol%, 1.9mol%, 2mol%, such as 1mol%, or a range value formed by any two of them, such as 1mol%~1.5mol%, of the mass percentage of elements (Ni+Co+Mn+M') in the precursor.

[0065] The particle size of the coating is small enough to be uniformly coated after high-speed mixing; the atmosphere of the third sintering is N2or Ar.

[0066] The third aspect of the present application provides a lithium ion secondary battery, the preparation raw material of the lithium ion secondary battery includes the lithium ion battery positive electrode material of the first aspect of the present application or the lithium ion battery positive electrode material prepared by the method of the second aspect of the present application. BRIEF DESCRIPTION OF DRAWINGS

[0067] Figure 1 It is the SEM diagram of the positive electrode material prepared in Example 1.

[0068] Figure 2DCR impedance of the positive electrode material prepared in Example 1-5 and Comparative Example 1-3.

[0069] Figure 3 XRD refinement pattern of the lithium ion battery positive electrode material obtained in Example 1. DETAILED DESCRIPTION

[0070] The following are specific embodiments of the present application, and the technical solutions of the present application are further described in combination with the embodiments, but the present application is not limited to these embodiments.

[0071] In a first aspect, some embodiments of the present application provide a lithium ion battery positive electrode material having a core-shell structure, from the center to the surface of the lithium ion battery positive electrode material, a lithium layered metal oxide, a composite dual-phase coating layer and a carbon coating layer are distributed, and the preparation raw materials of the composite dual-phase coating layer include a fast ion conductor and an oxide.

[0072] In the prior art, the development of lithium ion battery positive electrode materials has evolved from single components to composite structures. Early commercialized materials such as lithium iron phosphate and lithium cobaltate are difficult to meet the high-end demand due to energy density or cost limitations, and although ternary materials have high energy density, they are prone to structural phase change during the cycle process, leading to capacity attenuation, surface residual lithium causing side reactions, and insufficient high-temperature stability. The existing surface coating technology mostly uses a single fast ion conductor or conductive material, which is difficult to balance the coordination optimization of ion conduction and electron transmission, and the insufficient interface bonding strength of the coating layer limits the long-term stability of the material.

[0073] In order to solve the above problems, researchers found that a single coating material cannot solve the contradiction between ion diffusion and electron conduction at the same time, and tried to achieve functional complementation by constructing a multi-layer coating structure. Through experimental verification, the composite coating of fast ion conductor and oxide can form a stable interface layer, but the uniformity of the coating layer is still not ideal. Further research found that by controlling the crystallinity of the coating layer through a staged sintering process, combined with the outer coating of carbon material, the overall conductivity can be effectively improved.

[0074] Therefore, the present application provides a lithium ion battery positive electrode material with a core-shell structure, from the center to the surface, a lithium layered metal oxide, a composite dual-phase coating layer and a carbon coating layer are distributed in turn, and the composite dual-phase coating layer is composed of a fast ion conductor and an oxide.

[0075] The core-shell structure refers to a layered structure extending from the center to the outside, the center layer is a lithium layered metal oxide for carrying out electrochemical activity, the intermediate layer is a composite double-phase coating layer with ion conduction and structural stability functions, and the outer layer is a carbon coating layer for improving electron transmission. The fast ion conductor in the composite double-phase coating layer can be selected from a NASICON type material with three-dimensional ion channels, such as lithium zirconium phosphate, and the oxide can be selected from tungsten oxide, aluminum oxide or zirconium oxide, and the two form an interpenetrating network structure through high-temperature solid-phase reaction. The carbon coating layer can form a continuous conductive network through pyrolysis of an organic carbon source, such as an amorphous carbon layer formed by high-temperature carbonization of glucose.

[0076] Specifically, the lithium layered metal oxide is used as the main material for electrochemical reaction, and the layered structure provides lithium ion intercalation / deintercalation channels. The composite double-phase coating layer reduces the interface impedance through the fast lithium ion transmission characteristics of the fast ion conductor, and the oxide component fills the interstitial gaps between the grain boundaries of the fast ion conductor to inhibit the penetration of the electrolyte. The carbon coating layer forms a continuous electron path on the surface of the material to accelerate the charge transfer reaction. The three-layer structure realizes interface chemical bonding through gradient sintering process, the composite coating layer of the fast ion conductor and the oxide forms a eutectic structure in the secondary sintering, and the carbon coating layer is uniformly deposited on the surface in the third sintering.

[0077] Compared with the prior art, the difference in the thermal expansion coefficient between the fast ion conductor and the substrate material in the traditional single-layer coating scheme easily leads to cracking of the coating layer, while the composite double-phase coating layer buffers the thermal stress through the oxide dispersion phase to maintain the integrity of the coating layer. The existing carbon coating process mostly uses a single carbon source for direct coating, and the present scheme performs carbon deposition on the surface of the composite coating layer, which can avoid the penetration of carbon materials into the substrate to damage the crystal structure.

[0078] Through the above technical scheme, the present application effectively suppresses the side reaction of residual lithium on the surface of the positive electrode material and the electrolyte, the composite double-phase coating layer maintains structural stability during the cycle process, the carbon coating layer continuously provides an electron transmission path, and the three-layer synergistic effect makes the material discharge 50 cycles at 2C rate with a cycle retention rate of 96.5%, and the capacity attenuation rate after high-temperature storage for 60 days is controlled within 5%.

[0079] In combination with the first aspect, in some embodiments of the present application, the chemical formula of the lithium layered metal oxide is Li a Ni x Co y Mn z M w O2, wherein 1.03≤a≤1.3, 0.3≤x≤0.8, preferably 0.3≤x≤0.6, 0≤y≤0.4, 0≤z≤0.4, 0≤w≤0.1, x+y+z+w=1, and M contains at least one of Zr, W, Ti, Al, Nb, La, Sr, Ca, B, Ba, Mo and Ta.

[0080] Chemical formula Li a Ni x Co y Mn z M w The lithium content a in O2 is controlled in the range of 1.03 to 1.3, and specifically lithium carbonate or lithium hydroxide can be used as the lithium source, and the molar ratio of lithium to transition metal is adjusted to achieve this. This range can balance the structural stability and capacity during lithium deintercalation, avoiding excessive lithium leading to increased residual lithium or structural collapse. The nickel content x is limited to 0.3 to 0.8, and specifically the ratio of nickel, cobalt and manganese in the precursor can be adjusted to achieve this, increasing the nickel content can improve the capacity, and the lower limit control can inhibit the surface side reaction of the material. The cobalt content y and the manganese content z are limited in the range of 0 to 0.4 respectively, and specifically the co-precipitation method can be used to prepare the precursor, and by reducing the ratio of cobalt and manganese, the cost is reduced and the dissolution of transition metals is reduced. The doping element M contains at least one of Zr, W, Ti, Al, Nb, La, Sr, Ca, B, Ba, Mo and Ta, and specifically zirconium oxide or tungsten oxide can be used as the doping source, and by lattice doping, the structural phase transition during the cycle process is inhibited and the ion diffusion rate is improved.

[0081] Specifically, by accurately adjusting the molar ratio of lithium to transition metal, the lithium layered metal oxide can maintain a stable layered structure during charging and discharging, reducing lattice distortion caused by excessive or insufficient lithium. The lower limit of the nickel content can avoid the problem of insufficient capacity of low-nickel materials, while the upper limit control can alleviate the resulting surface instability and residual lithium accumulation. The limitation of cobalt and manganese content reduces the cost while stabilizing the bulk phase structure of the material through synergistic effect. The doping element M occupies the transition metal site or forms a surface passivation layer, inhibiting the generation of oxygen vacancies during the cycle process, thereby reducing the direct current impedance and improving the high temperature stability.

[0082] Compared with the prior art, the existing ternary material usually adopts a fixed ratio of nickel, cobalt and manganese or single element doping, for example, patent CN110690435A only improves the performance by surface coating, without involving bulk phase doping and synergistic optimization of element ratio. This scheme limits the nickel content range and combines multi-element doping, while maintaining high capacity, and multi-dimensionally inhibiting structural degradation from the bulk phase to the surface, solving the problems of cycle decay and impedance rise caused by imbalance of element ratio in the prior art.

[0083] By the technical scheme, the balance between the structural stability and the electrochemical performance of the lithium layered metal oxide is achieved. By controlling the nickel content range, the surface residual lithium is reduced while the high capacity is ensured; by limiting the cobalt and manganese content, the material cost is reduced and the transition metal dissolution is inhibited; by the multi-element doping, the lattice structure is optimized, the lithium ion diffusion rate is improved, and the phase change in the cycle process is inhibited. The scheme effectively alleviates the defects of the material in the cycle life and the rate performance, and provides a material basis for the development of high-power lithium ion batteries.

[0084] In some embodiments of the first aspect, 0.02≤w≤0.06.

[0085] In some embodiments of the first aspect, M comprises at least one of Zr, W, Ti.

[0086] In some embodiments of the first aspect, the composite dual-phase coating layer is obtained by sintering the fast ion conductor and the oxide.

[0087] During the sintering process, part of the oxide, such as Al2O3 or WO3, becomes lithium aluminate or lithium tungstate, which plays a role in ion conduction; part of the oxide remains in its original state, which plays a role in electron conduction.

[0088] In some embodiments of the first aspect, the fast ion conductor comprises at least one of a NASICON-type fast ion conductor, a LISICON-type fast ion conductor, and a perovskite-type fast ion conductor.

[0089] Specifically, by selecting a NASICON-type, LISICON-type, or perovskite-type fast ion conductor as the composition of the composite dual-phase coating layer, a stable ion transport network can be formed on the surface of the material. For example, during the secondary sintering process, the fast ion conductor and the oxide are jointly coated on the surface of the lithium layered metal oxide, and the high ion conductivity of the fast ion conductor can accelerate the diffusion of lithium ions during charging and discharging, while the composite coating layer formed with the oxide can inhibit the interface side reaction. In addition, the crystal structure of the fast ion conductor has high lattice matching with the lithium layered metal oxide, which can enhance the bonding strength of the coating layer and the core layer material, and avoid the shedding of the coating layer during the cycle process.

[0090] Compared with the prior art, the prior art usually uses a single type of fast ion conductor (such as only using a perovskite-type material), which has limitations in ion transport path and interface stability. However, by utilizing the synergistic effect of the fast ion conductor and the oxide, the advantages of three-dimensional ion channels and layered transport structures can be utilized at the same time, and the lithium ion diffusion kinetics is further optimized. In addition, the composite coating strategy of the fast ion conductor and the oxide compensates for the defects that the ion conductivity and the structural stability are difficult to be considered in the traditional single coating layer.

[0091] By the technical solution, the interface impedance of the positive electrode material of the lithium ion battery can be effectively reduced, the high-rate charge and discharge performance is improved, the combination strength of the coating layer and the core layer material is enhanced, the loss of the active substance in the cycle process is reduced, and thus the cycle life of the battery is prolonged.

[0092] In combination with the first aspect, in some embodiments of the present application, the NASICON type fast ion conductor is a fast ion conductor material taking ions as carriers, and the name is derived from its high ion conductivity. This kind of material can realize the rapid migration of ions due to its three-dimensional open framework structure.

[0093] In combination with the first aspect, in some embodiments of the present application, the NASICON type fast ion conductor comprises at least one of lithium aluminum titanium phosphate (LATP), lithium zirconium phosphate (LZP), lithium phosphate and lithium aluminate.

[0094] In combination with the first aspect, in some embodiments of the present application, the LISICON type fast ion conductor is a solid-state electrolyte taking lithium ions as carriers, and the chemical composition takes lithium as the core, and can also contain aluminum, germanium, phosphorus, oxygen, sulfur, selenium, silicon, titanium, arsenic, chromium and other elements.

[0095] In combination with the first aspect, in some embodiments of the present application, the LISICON type fast ion conductor comprises LiZnGeO4, Li 3.5 Si 0.5 P 0.5 O4, Li 10 AlP2O 12 at least one of.

[0096] In combination with the first aspect, in some embodiments of the present application, the perovskite type fast ion conductor is a kind of material taking perovskite structure (ABX3) as the basis, and is named because of its special crystal framework structure which can realize the rapid migration of ions (such as oxygen ions, protons or lithium ions). This kind of material shows excellent ion conductivity under high temperature or specific doping conditions.

[0097] In combination with the first aspect, in some embodiments of the present application, the perovskite type fast ion conductor comprises Li 3x La 0.67- x TiO3, Li 3x Nd 0.67-x TiO3, La x Ag y Li 1-3x-y NbO3 at least one.

[0098] In combination with the first aspect, in some embodiments of the present application, the fast ion conductor is a NASICON type fast ion conductor.

[0099] In some embodiments of the first aspect, the oxide includes at least one of oxides of Zr, W, Ti, Al, and Nb.

[0100] The oxide refers to an inorganic compound formed by the combination of a metal element and oxygen, which can be realized by using one or more combinations of zirconium oxide, tungsten oxide, titanium oxide, aluminum oxide, or niobium oxide. For example, tungsten oxide can be used as an auxiliary component of fast ion conductor to form a stable interface layer through high-temperature sintering, thereby inhibiting the side reaction between the material surface and the electrolyte; aluminum oxide can preferentially react with residual lithium to generate an inert compound, thereby reducing the loss of active lithium.

[0101] Specifically, the introduction of the oxide into the composite dual-phase coating layer can form a synergistic effect with the fast ion conductor. The oxide partially melts during high-temperature sintering, filling the gaps between the fast ion conductor particles and forming a continuous and dense protective layer. This composite structure not only blocks the corrosion of the electrolyte to the core material, but also improves the lithium ion diffusion kinetics by adjusting the ion / electron mixed conductive properties of the coating layer. For example, when aluminum oxide and zirconium oxide are used in combination, aluminum oxide preferentially consumes residual lithium on the surface, while zirconium oxide forms an interpenetrating network structure with the fast ion conductor during sintering, thereby enhancing the bonding strength between the coating layer and the substrate.

[0102] Compared with the prior art, the existing coating technology mainly uses a single type of oxide (such as only using aluminum oxide or zirconium oxide), which is difficult to meet the needs of residual lithium neutralization and interface stability. The present application selects a specific combination of metal oxides to construct a multi-level functional partition in the coating layer: the inner layer close to the substrate is mainly used for neutralizing residual lithium, and the outer layer is mainly used for mechanical protection and ion conduction. This layered design avoids the functional limitations of a single oxide, for example, the use of aluminum oxide alone can increase the brittleness of the coating layer, while the composite oxide system can balance the chemical stability and mechanical strength.

[0103] Through the above technical solutions, the present application effectively reduces the residual lithium content on the surface of the ternary material, inhibits the occurrence of interface side reactions during the cycle process, and at the same time, through the synergistic effect of the composite oxide and the fast ion conductor, the structural stability of the coating layer under high-temperature conditions is enhanced. Thus, on the basis of maintaining high capacity of the material, the rate performance and high-temperature cycle life of the lithium ion battery are significantly improved.

[0104] In some embodiments of the first aspect, the oxide includes at least one of oxides of W, Ti, and Al.

[0105] Among the oxides of W, Ti, and Al, tungsten oxide improves the overall performance of the battery by improving interface stability and material performance, and the oxide coating layer (such as WO3 and Al2O3) can improve the interface electron transport and improve the rate performance. The oxide has high mechanical strength and high chemical stability, which can inhibit the reaction between the electrode material and the electrolyte, and improve the stability of the battery.

[0106] WO3 will participate in the interface reaction during the sintering process to form lithium tungstate, but most of the tungsten oxide will remain to form a co-coating with the fast ion conductor.

[0107] In combination with the first aspect, in some embodiments of the present application, the carbon coating layer includes at least one of a graphene coating layer, a carbon nanotube coating layer, a glucose coating layer, and a sucrose coating layer.

[0108] Specifically, the carbon coating layer is constructed outside the composite dual-phase coating layer, forming a gradient coating structure. During charging and discharging, the high electronic conductivity of the carbon material forms a continuous electron transport path between active material particles, reducing the interface contact resistance. At the same time, the carbon layer and the inner layer fast ion conductor form a synergistic effect, the fast ion conductor promotes the rapid migration of lithium ions, and the carbon layer accelerates the electron conduction, which together reduces the electrode polarization. For example, when using graphene and carbon nanotube composite coating, the two-dimensional sheet and one-dimensional tubular structure interpenetrate to form a three-dimensional conductive network, which can improve the overall conductive efficiency without hindering the diffusion of lithium ions.

[0109] Compared with the prior art, the traditional single fast ion conductor coating scheme causes charge transport imbalance due to insufficient electronic conductivity, and only using metal oxide coating will hinder the diffusion of lithium ions. The present scheme combines the external carbon coating layer with the inner layer fast ion conductor, which not only maintains the smoothness of the lithium ion transport channel, but also establishes an efficient electron conduction path, solving the contradiction between ion conduction and electronic conduction in traditional technology.

[0110] Through the above technical scheme, the electronic conductivity of the positive electrode material is effectively improved, and the electronic transport efficiency between the electrode material particles is significantly improved under the condition of 2C discharging, and the polarization phenomenon in the charging and discharging process is significantly weakened. At the same time, the carbon coating layer physically protects the composite dual-phase coating layer, reducing the direct contact between the active material and the electrolyte during the cycle process, which helps to maintain the material structure stability. Under fast charging conditions, this structure design can ensure the synchronous performance of electronic fast transmission and lithium ion diffusion, so that the battery has excellent rate performance while maintaining high capacity.

[0111] In combination with the first aspect, in some embodiments of the present application, the carbon coating layer includes at least one of a graphene coating layer and a carbon nanotube coating layer.

[0112] Graphene and carbon nanotubes have ultra-high electronic conductivity (106 S / m) and two-dimensional continuous network structure, providing fast electron transmission channels for electrode materials and reducing interface charge transfer impedance.

[0113] Graphene is an inert material with stable chemical properties, and both tungsten oxide and graphene can reduce the interface side reaction between the electrode material and the electrolyte.

[0114] In combination with the first aspect, in some embodiments of the present application, the lithium ion battery positive electrode material has a porous structure. This is conducive to the full infiltration of the electrolyte and the rapid transmission of ions, reduces impedance, and improves power performance.

[0115] In combination with the first aspect, in some embodiments of the present application, in the porous structure of the lithium ion battery positive electrode material, part of the pores are through pores.

[0116] In the second aspect, in some embodiments of the present application, a method for preparing the lithium ion battery positive electrode material of the present application is provided, comprising the following steps:

[0117] (1) mixing and sintering a precursor Ni x Co y Mn z (OH)2, a lithium source, and a doping source containing M, performing primary sintering in an oxygen atmosphere, and cooling to obtain a primary sintered product;

[0118] (2) mixing the primary sintered product with a fast ion conductor and an oxide, and performing secondary sintering in an air atmosphere to obtain a secondary sintered product;

[0119] (3) mixing the secondary sintered product with a carbon coating agent, and performing tertiary sintering in a protective atmosphere to obtain a tertiary sintered product, i.e. the lithium ion battery positive electrode material of the present application.

[0120] Among them, the mixed sintering precursor Ni x Co y Mn z (OH)2 refers to a nickel-cobalt-manganese hydroxide precursor, which can be prepared by a coprecipitation method, and the element ratio can be adjusted to meet different capacity requirements. The lithium source can be lithium carbonate, lithium hydroxide, etc. compound, which is used to form a lithium layered metal oxide during sintering. The doping source containing M includes compounds of zirconium, tungsten, titanium, aluminum, and niobium, which can stabilize the crystal structure of the material through doping. The fast ion conductor can adopt NASICON type, LISICON type or perovskite type materials, such as Li 1.3 Al 0.3 Ti 1.7 (PO4)3, which is used to build a lithium ion fast transmission channel. The oxide includes zirconium oxide, aluminum oxide, etc., which forms a composite coating layer with the fast ion conductor to cooperatively improve the interface stability. The carbon coating agent can use organic substances such as glucose and sucrose, which are carbonized through sintering to form a conductive network.

[0121] Specifically, the first sintering is performed in an oxygen-containing environment, the precursor reacts with the lithium source to form a lithium metal oxide matrix with a layered structure, and the doping element M enters the lattice gap to inhibit structural distortion. The second sintering is performed in air, the fast ion conductor and the oxide are uniformly dispersed on the surface of the matrix to form a composite coating layer with ion conductivity and mechanical strength, wherein the fast ion conductor promotes lithium ion diffusion, and the oxide fills the pores to reduce electrolyte corrosion. The third sintering is performed in an inert atmosphere, a continuous carbon layer is formed by decomposition of the carbon coating agent, covering the outside of the composite coating layer, and a three-dimensional electron conduction path is constructed. The step-by-step sintering process controls the temperature gradient to avoid interference between different coating materials, and ensures the integrity and interface bonding strength of each functional layer.

[0122] Compared with the prior art, the traditional single coating process is prone to uneven distribution of the coating layer, and different coating materials may react at high temperatures. The step-by-step sintering strategy forms a gradient structure of the matrix, the composite coating layer and the carbon layer through three independent heat treatments, respectively. In the prior art, the fast ion conductor and the oxide are often mechanically mixed and coated simultaneously, which is prone to stress concentration at the interface, while the method forms a more dense composite coating layer by in-situ combination of the two materials through the second sintering. In addition, the existing carbon coating often uses a single carbon source for direct sintering, and the method can avoid the blockage of the ion transport channel by the carbon material after the ion conductive layer is constructed.

[0123] Through the above technical solutions, the problems of high surface residual lithium reactivity and poor bulk structure stability of the ternary positive electrode material are effectively solved. The composite dual-phase coating layer suppresses electrolyte decomposition while reducing the lithium ion diffusion barrier through the fast ion conductor, enhancing the interface mechanical strength through the oxide, and improving the overall electronic conductivity through the carbon layer. The step-by-step sintering process ensures the ordered construction of each functional layer, avoids interference between materials during high-temperature processing, and ultimately obtains a positive electrode material with high rate performance and long cycle stability.

[0124] In combination with the second aspect, in some embodiments of the present application, the sintering temperature of the first sintering is 700-900℃, and the time is 8-16h.

[0125] The sintering temperature of the first sintering refers to the reaction temperature range of the precursor, the lithium source and the doping source to form a layered oxide structure at high temperature, which can be realized by gradient heating or constant temperature sintering. This temperature range can ensure that the lithium source diffuses sufficiently and completes the solid-phase reaction with the transition metal precursor, while avoiding lattice distortion caused by too high temperature.

[0126] The sintering time refers to the duration of the heat treatment of the material in the target temperature range, which can be achieved by adjusting the atmosphere flow rate in the furnace or the material accumulation thickness. This time range can balance the reaction completion and energy consumption control, preventing uneven distribution of doped elements due to insufficient time or excessive particle growth due to excessive time.

[0127] Specifically, in the preparation of lithium layered metal oxides, the mixture of the precursor and the lithium source and the doping source is placed in an oxygen environment for heat treatment. When the temperature reaches 700℃ or above, lithium ions begin to diffuse into the transition metal oxide lattice, forming a stable layered structure; when the temperature exceeds 900℃, it may cause abnormal grain growth, destroying the uniformity of the material. If the sintering time is less than 8 hours, the lithium ions will not diffuse sufficiently, and unreacted lithium compounds may remain inside the material; if it exceeds 16 hours, it may cause excessive sintering between particles, reducing the specific surface area. By limiting the temperature and time within a certain range, the crystallinity of the material can be ensured while maintaining the regularity of the particle morphology.

[0128] Compared with the prior art, in the traditional ternary material preparation process, the one-time sintering temperature is usually lower than 750℃ or higher than 950℃, the former leading to incomplete lithiation reaction, and the latter causing rapid grain boundary migration and forming structural defects. Some existing methods use short-time high-temperature sintering (e.g., 5 hours / 950℃), which can shorten the production cycle but increase the amount of lithium residue on the material surface. The present application optimizes the synergistic relationship between temperature and time, avoiding grain coarsening and ensuring uniform distribution of doped elements in the lattice.

[0129] Through the above technical solutions, the present application can effectively control the crystallization process of layered oxides, reduce the internal lithium-nickel mixing phenomenon of the material, and thus reduce the impedance growth rate during battery cycling. At the same time, reasonable sintering parameter settings help to form a stable surface chemical state, inhibit the interface side reactions that occur in the subsequent coating process, and provide a structural basis for uniform deposition of the composite coating layer.

[0130] In combination with the second aspect, in some embodiments of the present application, the sintering temperature of the one-time sintering is any value in 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 770℃, 780℃, 790℃, 800℃, 810℃, 820℃, 830℃, 740℃, 850℃, 860℃, 880℃, 880℃, 890℃, 900℃, such as 800℃, or a range value formed by any two of them, such as 800℃-830℃.

[0131] When the sintering temperature of the primary sintering is too high, it may cause excessive grain growth or particle sintering agglomeration, increase the particle size difference, and cause cobalt / manganese element volatilization, destroy the material uniformity, form non-active phases (such as spinel phase) on the surface, and damage the rate performance and cycle life; when it is too low, it cannot fully complete the solid phase reaction, resulting in low material crystallinity, residual impurities, incomplete crystal structure, increased lithium-nickel mixing degree, and reduced lithium ion diffusion rate and initial discharge capacity.

[0132] In combination with the second aspect, in some embodiments of the present application, the sintering temperature of the secondary sintering is 400-600°C, and the time is 6-14 hours.

[0133] The secondary sintering temperature refers to the heat treatment temperature range required for the material to form a composite double-phase coating layer on the surface, which can be realized by gradient heating, for example, increasing to the target temperature at a rate of 3°C / min in an air environment. This temperature range can promote the solid phase reaction between the fast ion conductor and the oxide, and can also avoid excessive sintering to damage the core layer structure.

[0134] The secondary sintering time refers to the processing time for maintaining the target temperature, which can be realized by segmented heat preservation, for example, maintaining 8 hours at 500°C. This time range can ensure that the fast ion conductor and the oxide are fully reacted to form a continuous and dense coating layer, while preventing the loss of active lithium caused by long-time high-temperature treatment.

[0135] Specifically, in the preparation of the positive electrode material of the lithium ion battery, the product after the primary sintering is mixed with the fast ion conductor and the oxide, and then subjected to secondary sintering at a temperature of 400-600°C for 6-14 hours. Under this temperature condition, the lithium ion migration activity of the fast ion conductor is significantly improved, and an interface diffusion reaction occurs between the lithium ion conductor and the oxide particles, forming a composite coating layer with three-dimensional ion channels. Controlling the sintering time to be more than 6 hours can ensure the crystallinity of the coating layer, and controlling the sintering time to be less than 14 hours can effectively inhibit the excessive diffusion of transition metal elements to the coating layer.

[0136] Compared with the prior art, the conventional secondary sintering process usually uses a temperature higher than 700°C or a processing time shorter than 5 hours, which may easily cause the coating layer to have too high crystallinity and form a brittle interface, or the reaction to be insufficient and produce structural defects. The present application optimizes the synergistic effect of temperature and time parameters to form a moderate amorphous-crystalline composite structure of the coating layer, which not only ensures the continuity of the lithium ion transmission channel, but also improves the interface bonding strength between the coating layer and the core layer material.

[0137] By the technical scheme, the technical problem of insufficient interface bonding force of the composite dual-phase coating layer and the core layer material is effectively solved, and the formed coating layer has uniform thickness distribution and stable chemical structure. In the battery charging and discharging process, the structure can buffer the stress generated by volume change and inhibit the corrosion of electrolyte on the core layer material, thereby significantly improving the cycle stability and high-rate discharge performance of the positive electrode material.

[0138] In combination with the second aspect, in some embodiments of the application, the sintering temperature of the secondary sintering is any one of 400 DEG C, 420 DEG C, 440 DEG C, 460 DEG C, 480 DEG C, 500 DEG C, 520 DEG C, 540 DEG C, 560 DEG C, 580 DEG C, 600 DEG C, such as 500 DEG C, or a range value formed by any two, such as 500 DEG C-540 DEG C.

[0139] If the secondary sintering temperature is too low, the composite dual-phase coating layer cannot be uniformly formed or is too loose, and the interface side reaction is intensified, which affects the coating effect; if the secondary sintering temperature is too high, the oxide will undergo phase change to generate non-conductive electric impurities, which is not conducive to electronic conduction.

[0140] In combination with the first aspect, in some embodiments of the application, the sintering temperature of the third sintering is 450 DEG C-550 DEG C, and the time is 6h-14h.

[0141] The temperature range of the third sintering refers to the heat treatment condition in the process of forming the carbon coating layer, and specifically, a gradient temperature rising or constant temperature sintering mode can be adopted to realize the temperature range, which can promote the decomposition of the carbon coating agent and form a uniform carbon layer, and at the same time, avoid the destruction of the positive electrode material body structure due to too high temperature.

[0142] The time range of the third sintering refers to the reaction time required for forming the carbon coating layer, and specifically, the holding time of the sintering furnace can be controlled to realize the time range, which can ensure that the carbon coating agent is fully carbonized and stably combined with the surface of the secondary sintering product.

[0143] Specifically, the temperature and time parameters of the third sintering solve the problems of low interface bonding strength and discontinuous electronic conduction path of the carbon coating layer caused by improper sintering conditions in the prior art by adjusting the crystallinity and uniformity of the carbon coating layer. In this process, the temperature range is selected to be 450 DEG C-550 DEG C, for example, 480 DEG C or 520 DEG C, which can meet the carbonization needs of the carbon coating agent (such as glucose, sucrose) and avoid side reactions between the positive electrode material body and the carbon layer caused by too high temperature. The time range is set to be 6h-14h, for example, 8h or 12h, which can ensure that the carbon coating agent is fully pyrolyzed and forms a continuous conductive network, and at the same time, avoid material particle agglomeration or increase of lattice defects caused by too long time.

[0144] In some embodiments, the third sintering can be performed in a segmented temperature control manner, for example, first at 450℃ for 2h, and then at 550℃ for 4h, to optimize the graphitization degree of the carbon layer. The carbon coating agent can be a mixture of glucose and carbon nanotubes, which is mechanically mixed and then sintered together with the second sintering product to form a composite carbon coating layer.

[0145] The present application balances the conductivity of the carbon layer and the stability of the interface by limiting the temperature and time range of the third sintering, while avoiding damage to the structure of the material body.

[0146] Through the above technical solutions, the present application can form a uniform and dense carbon coating layer, enhance the electron transport capacity between the positive electrode material particles, reduce the electrode polarization, and thus improve the rate performance and cycle stability of the lithium ion battery. In addition, the optimized sintering conditions can reduce the side reaction between the carbon layer and the electrolyte, inhibit the impedance increase during high-temperature cycling, and provide a reliable material basis for high-power battery applications.

[0147] In combination with the second aspect, in some embodiments of the present application, the sintering temperature of the third sintering is any one of 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, such as 500℃, or a range value formed by any two, such as 480℃-520℃.

[0148] If the third sintering temperature is too high, the two-dimensional structure of graphene will be damaged, resulting in a decrease in conductivity and mechanical strength. If it is too low, the coating effect will be poor, and a heterojunction interface cannot be formed, thereby reducing the interface bonding effect of the composite material.

[0149] The present application uses a high-temperature solid-phase method to form a composite double-phase coating layer in a suitable temperature range. Lithium layered oxides, oxides, and fast ion conductors are mixed at high speed, diffused at high temperature, and the interface is reconstructed, and finally a co-coating layer is formed on the surface of the electrode particles.

[0150] In combination with the second aspect, in some embodiments of the present application, in step (1), the molar percentage of the added doping element M in the elements (Ni+Co+Mn+M') in the precursor is 0.06mol%-1.5mol%.

[0151] In combination with the second aspect, in some embodiments of the present application, in step (1), the molar percentage of the added doping element M in the elements (Ni+Co+Mn+M') in the precursor is 0.08mol%-1mol%.

[0152] In some embodiments of the second aspect, in step (1), the added doping element M accounts for any one of 0.08 mol%, 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.4 mol%, 0.5 mol%, 0.6 mol%, 0.7 mol%, 0.8 mol%, 0.9 mol%, 1 mol%, or a range formed by any two of them, such as 0.5 mol%~0.7 mol%, of the mole percentage of elements (Ni+Co+Mn+M’) in the precursor.

[0153] In some embodiments of the second aspect, in step (2), the added coating source accounts for 0.06 mol%~2 mol% of the mole percentage of elements (Ni+Co+Mn+M’) in the precursor.

[0154] In some embodiments of the second aspect, in step (2), the added coating source accounts for 0.08 mol%~1.5 mol% of the mole percentage of elements (Ni+Co+Mn+M’) in the precursor.

[0155] In some embodiments of the second aspect, in step (2), the added coating source accounts for any one of 0.08 mol%, 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.4 mol%, 0.5 mol%, 0.6 mol%, 0.7 mol%, 0.8 mol%, 0.9 mol%, 1 mol%, 1.1 mol%, 1.2 mol%, 1.3 mol%, 1.4 mol%, 1.5 mol%, or a range formed by any two of them, such as 1 mol%~1.5 mol%, of the mole percentage of elements (Ni+Co+Mn+M’) in the precursor.

[0156] In some embodiments of the second aspect, in step (3), the added coating source accounts for 0.05 wt%~0.5 wt% of the mass percentage of elements (Ni+Co+Mn+M’) in the precursor.

[0157] In some embodiments of the second aspect, in step (3), the added coating source accounts for 0.08 mol%~0.2 wt% of the mass percentage of elements (Ni+Co+Mn+M’) in the precursor.

[0158] In some embodiments of the second aspect, in step (3), the added coating source accounts for 0.08 mol%, 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.4 mol%, 0.5 mol%, 0.6 mol%, 0.7 mol%, 0.8 mol%, 0.9 mol%, 1 mol%, 1.1 mol%, 1.2 mol%, 1.3 mol%, 1.4 mol%, 1.5 mol%, 1.6 mol%, 1.7 mol%, 1.8 mol%, 1.9 mol%, 2 mol% of the mass percentage of elements (Ni+Co+Mn+M') in the precursor, such as 1 mol%, or a range formed by any two of them, such as 1 mol% to 1.5 mol%.

[0159] In the third aspect, some embodiments of the present application provide a lithium ion secondary battery, and the raw material for preparing the lithium ion secondary battery includes the lithium ion battery cathode material of the first aspect of the present application or the lithium ion battery cathode material prepared by the method of the second aspect of the present application.

[0160] The lithium ion secondary battery refers to a secondary battery with a lithium ion intercalation compound as a cathode active material, and can be implemented by using a battery system containing a core-shell structure cathode material, which improves the ion and electron transmission path through a multi-layer coating structure.

[0161] The raw material for preparing the lithium ion battery cathode material refers to a layered oxide material with a composite coating layer used as a cathode active material, which can be prepared by a three-time sintering process, and the material reduces the interface impedance through the synergistic effect of fast ion conductors and oxides.

[0162] The carbon coating layer refers to a carbon-based conductive layer covering the surface of the cathode material, which can be implemented by using graphene or carbon nanotubes, etc., and the layer optimizes the electrode reaction kinetics by improving the electronic conduction capacity.

[0163] Specifically, the cathode active material of the lithium ion secondary battery uses a layered oxide material with a core-shell structure, the core of which is a nickel-cobalt-manganese-based lithium metal oxide, the intermediate layer is a composite coating layer of fast ion conductors and oxides, and the outer layer is a carbon material. During the charging and discharging process, the fast ion conductors accelerate the diffusion of lithium ions through the three-dimensional ion channels, the oxides inhibit the surface side reactions through the chemical stability, and the carbon layer promotes the electron transmission through the continuous conductive network. In the three-time sintering process, the fast ion conductors and oxides form a uniform composite coating layer in the secondary sintering stage, and the carbon layer completely covers the surface of the material in the third sintering stage, forming a gradient functional structure.

[0164] Compared with the prior art, the existing ternary material is mostly coated with a single fast ion conductor or metal oxide, and it is difficult to simultaneously optimize the ion and electron transmission performance. The scheme combines the high ion conductivity of the fast ion conductor with the interface stability characteristics of the oxide through the composite two-phase coating layer, and the carbon coating layer of the outer layer makes up for the defects of the insufficient electronic conductivity of the fast ion conductor. The three sintering processes control the temperature in stages, so that the coating layers form a tightly bonded interface structure, avoiding the problem of uneven distribution of materials in the traditional mixed coating.

[0165] Through the above technical scheme, the present application solves the problems of limited rate performance and poor cycle stability of the ternary material, improves the capacity retention rate of the lithium ion battery under high-power charging and discharging conditions, and suppresses the interface side reaction between the electrode material and the electrolyte, thereby prolonging the service life of the battery.

[0166] Test results show that the electrode material of the present application has a DCR impedance of 200Ω at -30℃, a lithium occupancy rate of 97.2%, and a cycle retention rate of ≥97.5.

[0167] The concept and technical effects of the present application will be described below in conjunction with the embodiments to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, not all embodiments. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0168] In the description of the present application, the description of the terms "one embodiment", "some embodiments", "illustrative embodiment", "example", "specific example" or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0169] Unless otherwise specified, "room temperature" in the present application means 25℃±5℃.

[0170] Unless otherwise specified, "about" in the present application means that the allowable error is within ±2%.

[0171] Unless otherwise specified, the specific conditions in the embodiments are carried out according to the conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used are not marked with the manufacturer, but are conventional products that can be purchased on the market.

[0172] Example 1

[0173] A lithium ion battery anode material is prepared by the following steps:

[0174] (1) sintering precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2, Li2CO3 and Zr, W, Ti-containing doping source in an oxygen atmosphere, wherein the lithium metal ratio (molar ratio of Li to Ni+Co+Mn) is 1.12, the molar amount of the doping source accounts for 1 mol% of the total molar amount, one sintering is carried out in an oxygen atmosphere with an oxygen concentration > 98%, and the temperature is lowered to obtain a first sintering product, the sintering temperature of the first sintering is 850°C, and the sintering time is 12h;

[0175] wherein the Zr, W, Ti-containing doping source is WO3, ZrO2, TiO2 with a mass ratio of 2:2:1;

[0176] (2) mixing the obtained first sintering product with fast ion conductor LATP and tungsten oxide, the molar amount of LATP and tungsten oxide accounts for 0.08 mol% and 0.3 mol% of the total molar amount, respectively, secondary sintering is carried out in an air atmosphere, and the temperature is lowered to obtain a second sintering product, the sintering temperature of the secondary sintering is 500°C, and the sintering time is 10h;

[0177] (3) mixing the obtained second sintering product with graphene, the mass ratio of graphene accounts for 0.15wt%, tertiary sintering is carried out in a nitrogen atmosphere, and the temperature is lowered to obtain a third sintering product, the sintering temperature of the tertiary sintering is 500°C, and the sintering time is 10h.

[0178] Figure 1 is the SEM diagram of the anode material prepared in Example 1. From Figure 1 it can be seen that the surface of the particles is coated with a layer of material, which is a composite two-phase coating layer and graphene.

[0179] Example 2

[0180] A lithium ion battery anode material is prepared by the following steps:

[0181] (1) sintering precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2, Li2CO3 and Zr, W, Ti-containing doping source in an oxygen atmosphere, wherein the lithium metal ratio (molar ratio of Li to Ni+Co+Mn) is 1.12, the molar amount of the doping source accounts for 1 mol% of the total molar amount, one sintering is carried out in an oxygen atmosphere with an oxygen concentration > 98%, and the temperature is lowered to obtain a first sintering product, the sintering temperature of the first sintering is 850°C, and the sintering time is 12h;

[0182] The doping source containing Zr, W and Ti has a mass ratio of WO3, ZrO2 and TiO2 of 2:2:1;

[0183] (2) The first sintered product is mixed with fast ion conductor LZP and tungsten oxide, the molar ratio of LZP and tungsten oxide in the total molar amount is 0.08mol% and 0.3mol% respectively, secondary sintering is carried out in an air atmosphere, and cooling is performed to obtain a second sintered product, the sintering temperature of the secondary sintering is 500℃, and the sintering time is 10h;

[0184] (3) The second sintered product is mixed with graphene, the mass ratio of graphene in the total mass is 0.15wt%, tertiary sintering is carried out in a nitrogen atmosphere, and cooling is performed to obtain a third sintered product, the sintering temperature of the tertiary sintering is 500℃, and the sintering time is 10h.

[0185] Example 3

[0186] A lithium ion battery positive electrode material is prepared, and the steps are as follows:

[0187] (1) The precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2, Li2CO3 and the doping source containing Zr, W and Ti are mixed, the molar ratio of lithium metal to (Li to Ni+Co+Mn) is 1.12, the molar amount of the doping source accounts for 1mol% of the total molar amount, primary sintering is carried out in an oxygen atmosphere, the oxygen concentration is >98%, and cooling is performed to obtain a first sintered product, the sintering temperature of the primary sintering is 850℃, and the sintering time is 12h;

[0188] The doping source containing Zr, W and Ti has a mass ratio of WO3, ZrO2 and TiO2 of 2:2:1;

[0189] (2) The first sintered product is mixed with fast ion conductor LZP and tungsten oxide, the molar ratio of LZP and tungsten oxide in the total molar amount is 0.08mol% and 0.3mol% respectively, secondary sintering is carried out in an air atmosphere, and cooling is performed to obtain a second sintered product, the sintering temperature of the secondary sintering is 500℃, and the sintering time is 10h;

[0190] (3) The second sintered product is mixed with graphene, the mass ratio of graphene in the total mass is 0.15wt%, tertiary sintering is carried out in a nitrogen atmosphere, and cooling is performed to obtain a third sintered product, the sintering temperature of the tertiary sintering is 500℃, and the sintering time is 10h.

[0191] Example 4

[0192] The difference from Example 1 is that the precursor Ni0.33 Co 0.33 Mn 0.33 (OH)2, except that the same as example 1.

[0193] Example 5

[0194] The difference from example 1 is that the precursor Ni 0.6 Co 0.2 Mn 0.2 (OH)2, except that the same as example 1.

[0195] Comparative example 1

[0196] The difference from example 1 is that no fast ion conductor is added in step two.

[0197] Comparative example 2

[0198] The difference from example 1 is that no oxide is added in step two.

[0199] Comparative example 3

[0200] The difference from example 1 is that there is no step three.

[0201] Test example

[0202] This example tests the XRD pattern of the lithium ion battery positive electrode material obtained in example 1 Figure 3 ), and the occupancy of lithium ions and the grain diameter are calculated by refining, and the refining software is Fullprof; wherein the detection equipment of XRD pattern is Japan Rigaku XRD tester, the model is smartlab 3kw; the grain diameter is read by the function of XRD tester, wherein the grain diameter is the average value of the grain diameter of the characteristic peak of 0°-70°. The test results show that the grain diameter of the lithium ion battery positive electrode material obtained in example is between , which ensures the integrity and structural stability of the crystal.

[0203] This example also tests the oil absorption of the lithium ion battery positive electrode material obtained in examples 1-3 and comparative examples 1-3, and the specific detection equipment is HITEC DABS oil absorption tester, the paraffin oil is dropped at a constant speed during the stirring process of the lithium ion battery positive electrode material, and the oil absorption is calculated according to the torque value.

[0204] This example also tests the particle size of the lithium ion battery positive electrode material obtained in examples 1-3 and comparative examples 1-3, and calculates the span value, the particle size is tested by Malvern laser particle size analyzer, if no special instruction, the particle size in the present application is the volume cumulative particle size, for example, D 50 , actually D V50The span value = (D90-D10) / D50 was calculated. The results show that the span value of the lithium ion battery cathode material obtained in the examples is between 0.4 and 1.4, and further mainly concentrates between 0.6 and 0.8. That is, the lithium ion battery cathode material obtained has high particle size uniformity.

[0205] The low temperature impedance and electrochemical performance of the lithium ion battery cathode materials obtained in Examples 1-3 and Comparative Examples 1-3 were also tested. The test steps included:

[0206] A button cell was prepared, and the lithium ion battery cathode material: conductive agent SuperP, binder polyvinylidene fluoride (PVDF) were mixed and stirred uniformly at a mass ratio of 90:5:5 with N-methyl pyrrolidone (NMP) to form a positive electrode slurry (solid content about 40%), which was coated on the current collector aluminum foil, dried at 105°C, and then rolled at room temperature to a surface density of 2.8-3.3 g / cm 3 , and then punched and cut into φ14 mm round pieces to form a positive electrode sheet. The button cell was assembled in a glove box. The button cell was assembled in the order of "negative shell-foam nickel-lithium sheet (φ18 mm)-8 drops of electrolyte-separator (φ22 mm, thickness 16 μm)-8 drops of electrolyte-positive electrode sheet-positive shell", wherein the electrolyte was composed of ethylene carbonate (EC), methyl ethyl carbonate (EMC) and dimethyl carbonate (DMC) (EC:EMC:DMC volume ratio = 1:1:1) containing 1.0 M LiPF6; the size of the battery shell (positive shell and negative shell) was 24 mm. The assembled button cell was placed in the mold groove of a hydraulic sealing machine (purchased from Shenzhen Keyi Zhida Technology Co., Ltd.), locked, and the pressure was >450 kg / cm 2 , then unlocked, and the sealed button cell was taken out.

[0207] Impedance (DCR) test:

[0208] At 25°C, the charge-discharge cycle characteristics of the button cell were detected by using a blue and test cabinet, and the charge-discharge rate was 0.1C, and the voltage interval was 2.8V-4.25V. Specifically, 0.1C constant current charging to 4.25V, then constant voltage charging to 0.02C cutoff current at 4.25V, standing for 5min, 0.1C discharging to 2.8V, standing for 5min. Then 0.1C constant current charging to 4.25V, then constant voltage charging to 0.02C cutoff current at 4.25V, standing for 5min, 0.1C discharging for 5h, then standing for 2h, then detecting the low temperature impedance at -30°C by using a blue and test cabinet, standing for 1h at -30°C, then 2C discharging for 10s, then standing, the voltage difference between 2C discharging and discharging for 10s was divided by the discharging current, and the DCR value at -30°C was obtained.

[0209] Test of capacity retention rate:

[0210] The charge-discharge cycle characteristics of the button cell were detected by a blue light test cabinet at 25℃, and 1C=163 mAh / g was set. The charge-discharge was carried out at a voltage interval of 2.8V-4.25V at a charge rate of 1C and a discharge rate of 2C, specifically, charged at 1C to 4.25V, then charged at 4.25V to the cut-off current of 0.02C, rested for 5min, discharged at 2C to 2.8V, rested for 5min, and the charge-discharge capacity after the first cycle was recorded. As above, the cycle was carried out in turn, and after 50 cycles of charge-discharge, the charge-discharge capacity after the 50th cycle was recorded.

[0211] Cycle capacity retention rate (%)=(50th cycle discharge capacity / 1st cycle discharge capacity)×100%.

[0212] The results of the above tests are shown in Table 1.

[0213] Table 1 Performance of the positive electrode material of the lithium ion battery obtained in Examples 1-5 and Comparative Examples 1-3

[0214] Example -30 °C impedance value (Ω) Lithium occupancy rate (%) Oil absorption amount (ml / 100 g) Capacity retention rate (%) Example 1 198 97.2 45.6 97.6 Example 2 200 97.6 44.8 97.5 Example 3 195 97.5 46.9 97.8 Example 4 205 98.5 44.2 97.9 Example 5 192 97.6 44.7 97.6 Comparative Example 1 356 96.5 42.5 96.5 Comparative Example 2 319 96.6 43.1 96.3 Comparative Example 3 367 96.8 42.0 96.2

[0215] According to the above results, it can be known that the positive electrode material prepared in the present application has lower DCR impedance.

[0216] As can be known from the above, in the positive electrode material of the lithium ion battery, a synergistic effect occurs between the structures and components, and in the preparation method provided by the present application, a synergistic effect occurs between the step sequence and parameters, which together improves the comprehensive performance of the obtained positive electrode material of the lithium ion battery.

[0217] The present application has been described in detail above with reference to the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by a person skilled in the art without departing from the purpose of the present application.

Claims

1. A lithium-ion battery cathode material, characterized in that, The lithium ion battery cathode material has a core-shell structure, from the center to the surface of the lithium ion battery cathode material, there are lithium layered metal oxide, composite two-phase coating layer and carbon coating layer, the preparation raw material of the composite two-phase coating layer includes fast ion conductor and oxide.

2. The lithium-ion battery cathode material of claim 1, wherein, The lithium layered metal oxide has a chemical formula of Li a Ni x Co y Mn z M w O2, wherein 1.03≤a≤1.3, 0.3≤x≤0.8, 0≤y≤0.4, 0≤z≤0.4, 0≤w≤0.1, x+y+z+w=1, and M comprises at least one of Zr, W, Ti, Al, Nb, La, Sr, Ca, B, Ba, Mo, and Ta.

3. The lithium-ion battery cathode material of claim 1 or 2, wherein, The fast ion conductor includes at least one of NASICON type fast ion conductor, LISICON type fast ion conductor and perovskite type fast ion conductor.

4. The lithium-ion battery cathode material of claim 1 or 2, wherein, The oxide includes at least one of Zr, W, Ti, Al and Nb oxide.

5. The lithium-ion battery cathode material of claim 1 or 2, wherein, The carbon coating layer includes at least one of graphene coating layer, carbon nanotube coating layer, glucose coating layer and sucrose coating layer.

6. A method of preparing the lithium-ion battery cathode material of any one of claims 1 to 5, characterized in that, The method includes the following steps: (1) mixing and sintering precursor Ni x Co y Mn z (OH)2, a lithium source and a doping source containing M, sintering once in an oxygen atmosphere, and cooling to obtain a sintered product; (2) mixing the first sintering product, fast ion conductor and oxide, and performing secondary sintering in air atmosphere to obtain secondary sintering product; (3) mixing the secondary sintering product with carbon coating agent, and performing third sintering in protective atmosphere to obtain third sintering product, i.e. the lithium ion battery cathode material.

7. The method of claim 6, wherein, The sintering temperature of the first sintering is 700-900℃, and the time is 8-16h.

8. The method of claim 6, wherein, The sintering temperature of the secondary sintering is 400-600℃, and the time is 6-14h.

9. The method of claim 6, wherein, The sintering temperature of the third sintering is 450-550℃, and the time is 6-14h.

10. A lithium-ion secondary battery, characterized by comprising: The preparation raw material of the lithium ion secondary battery includes the lithium ion battery cathode material according to any one of claims 1-5 or the lithium ion battery cathode material prepared by the method according to any one of claims 6-9.

Citation Information

Cited By

  • Lithium-rich manganese-based positive electrode material with core-shell-shell structure and preparation method of lithium-rich manganese-based positive electrode material

    CN121862720A